Kerjasama Antara Pemerintah Kabupaten Kubu Raya Dengan Pemerintah Kabupaten Madiun Dalam Persiapan Pelaksanaan Program Transmigrasi (Studi Pada Dinas Sosial, Tenaga Kerja Dan Transmigrasi Kabupaten Kubu Raya) - Wulandari, Mentari (Jurnal Administrasi Publik, 2014)
Abstract: Intergovernmental Cooperation the Local Government of Kubu Raya Regency and The Local Government of Madiun Regency in Preparation of Implementation Transmigrastion Program. The transmigration program is an alternative solution to overcome the problems of population and as an effort to spur equitable development in Indonesia. In order for these objectives to be realized then The Local Government of Kubu Raya Regency and The Local Government of Madiun Regency preparing the implementation of the resettlement program to the fullest by establishing cooperative relationships between local. The partnership established through the preparation process of cooperation, assessment of cooperation, discussion and signing of a cooperation agreement and the process of preparation of the transmigration program. In the process of cooperation embodied the principles of cooperation shows that the preparation of the implementation of the transmigration program was organized with the involvement of multiple stakeholders in the area, so that the transmigration program was organized with attention to local needs and the support of community. In order transmigration program may be optimized so The Local Government of Kubu Raya Regency and The Local Government of Madiun Regency still need to enhance the role of stakeholders in the area sharing and allocation of local budget funds for the preparation of the implementation of the transmigration program.Keywords: Intergovernmental Cooperation the Local Government, Preparation of Implementation Program, Transmigrastion ProgramAbstrak: Kerjasama antara Pemerintah Kabupaten Kubu Raya dengan Pemerintah Kabupaten Madiun dalam Persiapan Pelaksanaan Program Transmigrasi. Program transmigrasi merupakan solusi alternatif dalam mengatasi permasalahan kependudukan dan sebagai upaya memicu pemerataan pembangunan di Indonesia. Agar tujuan tersebut dapat terwujud maka Pemerintah Kabupaten Kubu Raya bersama Pemerintah Kabupaten Madiun melakukan persiapan pelaksanaan program transmigrasi secara maksimal dengan menjalin hubungan kerjasama antara daerah. Hubungan kerjsama ini terjalin melalui proses persiapan kerjasama, penjajakan kerjasama, pembahasan dan penandatanganan perjanjian kerjasama dan proses persiapan pelaksanaan program transmigrasi. Di dalam proses kerjasama tersebut terkandung prinsip-prinsip kerjasama yang menunjukan bahwa persiapan pelaksaan program transmigrasi diselenggarakan dengan melibatkan beberapa stakeholders di daerah, sehingga program transmigrasi diselenggarakan dengan memperhatikan kebutuhan daerah dan mendapat dukungan dari masyarakat. Agar program transmigrasi dapat berjalan secara optimal maka Pemerintah Kabupaten Kubu Raya dengan Pemerintah Kabupaten Madiun masih perlu meningkatkan peran stakeholders di daerah dan melakukan sharing alokasi dana APBD untuk penyelenggaraan persiapan pelaksanaan program transmigrasi.Kata kunci: kerjasama antara daerah, persiapan pelaksanaan program, Program Transmigrasi